Brain and Critical Thinking in Education: A Bibliometric Review and Wordcloud Analysis - Afridha Sesrita; Asep Supena; Mohamad Syarif Sumatri; Gumgum Gumelar; Firmanul Catur Wibowo (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis article uses data from the Scopus database for bibliometric review and wordcloud analysis visualization of publications related to Brain and Critical Thinking in Education (BCTE). The study highlights the importance of the brain in the learning process and critical thinking, as well as identifying research trends, key topics, and geographic distribution of authors over the decade 2013-2023. With a focus on English-language publications, the study reveals that "critical thinking" is the most frequently cited topic, with the United States as the most significant contributor. This analysis also suggests the need for further research that integrates brain-based learning with critical thinking to improve students' critical thinking and 21st-century skills in education. Understanding how the brain works will enable educators to design a comprehensive learning plan, including teaching materials, implementation, media, models, strategies, approaches, and appropriate methods, to achieve learning goals.AbstrakArtikel ini menggunakan data dari database Scopus untuk review bibliometrik dan visualisasi analisis wordcloud dari publikasi terkait Brain and Critical Thinking in Education (BCTE). Studi tersebut menyoroti pentingnya otak dalam proses pembelajaran dan berpikir kritis, serta mengidentifikasi tren penelitian, topik utama, dan distribusi geografis penulis selama dekade 2013-2023. Dengan fokus pada publikasi berbahasa Inggris, penelitian ini mengungkapkan bahwa “berpikir kritis” adalah topik yang paling sering dikutip, dengan Amerika Serikat sebagai kontributor paling signifikan. Analisis ini juga menyarankan perlunya penelitian lebih lanjut yang mengintegrasikan pembelajaran berbasis otak dengan berpikir kritis untuk meningkatkan pemikiran kritis siswa dan keterampilan abad 21 dalam bidang pendidikan. Memahami cara kerja otak akan memungkinkan pendidik merancang rencana pembelajaran yang komprehensif, meliputi bahan ajar, pelaksanaan, media, model, strategi, pendekatan, dan metode yang tepat, untuk mencapai tujuan pembelajaran.  How to Cite: Sesrita, A., Supena, A., Sumantri, M. S., Gumelar, G., & Wibowo, F. C. (2024). Brain and Critical Thinking in Education: A Bibliometric Review and Wordcloud Analysis. TARBIYA: Journal of Education in Muslim Society, 11(1), 65-80. doi:10.15408/tjems.v11i1.40506.